Hey, I'd like to give you a professional response.
First we need to re-group terms.
1. 2(3+g)−g=−4(g+1)
Let's also expand the terms.
6+2g−g=−4g−4
Simplify 6+2g-g to 6 + g.
6+g=-4g-4
Add 4g to BOTH sides.
6+2g−g=−4g−4
Simplify 6+g+4g to 6+5g.
6+5g=-4
Now subtract 6 from both sides.
5g = -4-6
Simplify -4 - 6 to -10.
Now you have 5g = -10.
g = -10/5 (Divide both sides by 5)
Simplify -10/5 to 2.
G = 2
Let's check our answer.
First let g = 2.
2+2 X (3-2) = -4 X (-2 + 1)
2 + 2 X 1 = -4 X (-2 +1)
2 + 2 X 1 = -4 x -1
2+2 = -(-4)
Remove the parentheses,
4 = 4 This problem has been checked.